Injuries over Neck due to Ligature Materials in case of Hanging of Varanasi Region of U.P. (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Background: Deaths by ligation of neck are in practice from the time immemorial  and before advent of civilization. In uncivilized societies, the application of ligation  for taking away the life of another person was one of the commonest practices which  were successfully carried out into the civilized societies. Hanging is that form of  violent asphyxial death in which ligature marks are found and it is mainly based on the  constricting forces which is : (i) either by the exclusion of air from lungs or oxygenated  blood from the brain, (ii) by means of ligature around the neck, (iii) the constricting  force is the weight of the body. Results: The data of present cross-sectional study  of 100 cases with the aim, injuries over neck due to ligature was collected from in  the Department of Forensic Medicine & Toxicology, Institute of Medical Science  (IMS), BHU, Varanasi, U.P. India. The total duration of sampling was six months and  different aspects such as sex ratio, age group involved, residence, ligature material  used type of hanging, place of hanging, the Position of the knot and other external  findings involved were taking under consideration. Conclusions: It was found that  the most common cause of death in Varanasi region was Socio-economic Status of the  victims with a male: female ratio of 1.8:1 with age group of 20- 29 years being most  commonly involved.
Keywords: Hanging; Ligature Mark; Ligature Material; Injuries to neck Skeleton